2022
DOI: 10.3389/fpubh.2022.877668
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy Among Older Adolescents and Young Adults: A National Cross-Sectional Study in China

Abstract: BackgroundWith promotion of COVID-19 vaccinations, there has been a corresponding vaccine hesitancy, of which older adolescents and young adults represent groups of particular concern. In this report, we investigated the prevalence and reasons for vaccine hesitancy, as well as potential risk factors, within older adolescents and young adults in China.MethodsTo assess these issues, an online survey was administered over the period from March 14 to April 15, 2021. Older adolescents (16–17 years old) and young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…The vaccination acceptance of younger people has also been reported in China (multiple logistic regression analysis: p = 0.003, OR = 0.93, 95% CI: 0.89–0.98) [ 14 ], where Zhang et al 2022 reported a higher prevalence of vaccine hesitancy among young adults aged 18 to 21 years compared to older adolescents 16 to 17 years (16.5% vs. 7.9%, p < 0.001) [ 13 ]. However, other studies have recorded no significant differences [ 9 , 10 , 18 ], while a trend that goes in the opposite direction as regards age was found in the Netherlands (80% 16–17 years vs. 68% 12–15 years), in line with a higher level of education, which implies a greater inclination to vaccination compared with a low level of education (78% vs. 64%) [ 12 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The vaccination acceptance of younger people has also been reported in China (multiple logistic regression analysis: p = 0.003, OR = 0.93, 95% CI: 0.89–0.98) [ 14 ], where Zhang et al 2022 reported a higher prevalence of vaccine hesitancy among young adults aged 18 to 21 years compared to older adolescents 16 to 17 years (16.5% vs. 7.9%, p < 0.001) [ 13 ]. However, other studies have recorded no significant differences [ 9 , 10 , 18 ], while a trend that goes in the opposite direction as regards age was found in the Netherlands (80% 16–17 years vs. 68% 12–15 years), in line with a higher level of education, which implies a greater inclination to vaccination compared with a low level of education (78% vs. 64%) [ 12 ].…”
Section: Discussionmentioning
confidence: 86%
“…According to Zhang et al 2022, however, the trend in vaccination adherence as age increases is then reversed, and vaccination hesitation has a higher prevalence in young adults between 18 and 21 than in older adolescents (16/17 years). Reasons for hesitation include underestimating the risks of infection, thinking that protection from innate immunity is sufficient, special physical conditions not suitable for vaccination, and conspiracy theories about vaccination, which are more common among young adults than older teenagers [ 13 ]. Cai et al 2021 reported that younger adolescents were more likely to vaccinate than older adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fact that immunosuppressants may affect the immunogenicity of the vaccine played a role in whether parents allowed their children to be vaccinated (43). The adolescents themselves believed that they had no risk of infection and that their symptoms would not be severe if they were infected (44). Adolescents with a history of immune-related diseases or other primary diseases in particular refused vaccination unless convincing evidence indicated clear benefits to them (42,44).…”
Section: Influence Of Population Heterogeneity On Vaccination Acceptancementioning
confidence: 99%
“…The adolescents themselves believed that they had no risk of infection and that their symptoms would not be severe if they were infected (44). Adolescents with a history of immune-related diseases or other primary diseases in particular refused vaccination unless convincing evidence indicated clear benefits to them (42,44). Moreover, clinical trials on the COVID-19 vaccine for adolescents (younger than 18) are still lacking and real-time dissemination of information on vaccine efficacy among adolescents is still limited.…”
Section: Influence Of Population Heterogeneity On Vaccination Acceptancementioning
confidence: 99%
“…With the promotion of various media and government policies, the COVID-19 vaccination rate in China is impressive, but further efforts are still required. Current studies reported many factors that contributed to COVID-19 vaccine hesitancy, such as the concerns of effectiveness, safety and the vague side-effect about the existing vaccine (12)(13)(14)(15). COVID-19 vaccine hesitancy presented to be a noteworthy public health issue.…”
Section: Introductionmentioning
confidence: 99%